2006
DOI: 10.1128/jb.188.7.2309-2324.2006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the Q Fever Agent,Coxiella burnetii, Assessed by Microarray-Based Whole-Genome Comparisons

Abstract: Coxiella burnetii, a gram-negative obligate intracellular bacterium, causes human Q fever and is considered a potential agent of bioterrorism. Distinct genomic groups of C. burnetii are revealed by restriction fragmentlength polymorphisms (RFLP). Here we comprehensively define the genetic diversity of C. burnetii by hybridizing the genomes of 20 RFLP-grouped and four ungrouped isolates from disparate sources to a high-density custom Affymetrix GeneChip containing all open reading frames (ORFs) of the Nine Mile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(150 citation statements)
references
References 86 publications
11
134
1
4
Order By: Relevance
“…The infection studies described here illustrate that there is pathotype diversity between C. burnetii isolates from different genogroups, and they are consistent with phylogenetic studies cataloging distinct gene contents (4). We therefore strove to determine whether this diversity was great enough to affect the ability of vaccines to protect against infection.…”
Section: Vol 77 2009mentioning
confidence: 84%
See 1 more Smart Citation
“…The infection studies described here illustrate that there is pathotype diversity between C. burnetii isolates from different genogroups, and they are consistent with phylogenetic studies cataloging distinct gene contents (4). We therefore strove to determine whether this diversity was great enough to affect the ability of vaccines to protect against infection.…”
Section: Vol 77 2009mentioning
confidence: 84%
“…These monophyletic groups supported the early RFLP groups and placed groups I, II, and III in one monophyletic group; group IV in the second monophyletic group; and group V in the third monophyletic group. A comprehensive microarray-based whole-genome comparison by Beare et al confirmed the relatedness of RFLP-grouped isolates and added two more genomic groups, VII and VIII (4). Differences in novel gene contents and pseudogenes may be factors in the variations in virulence seen among group I, IV, V, and VI isolates (5).…”
mentioning
confidence: 95%
“…O-antigen is the primary surface antigen recognized by Phase I antiserum [25]. Some, but not all, Phase II strains contain a chromosomal deletion eliminating roughly 20 genes associated with sugar metabolism [26][27][28]. Moreover, deep-rough LPS of Phase II strains can be antigenically distinct [29].…”
Section: Coxiella: a Wide-ranging Zoonotic Pathogenmentioning
confidence: 99%
“…All cRNA originating from Vero cell-propagated C. burnetii and 3 g cRNA from CCM-cultivated organisms were hybridized to a custom Affymetrix GeneChip designed as previously described (35). Microarray data were analyzed using Partek Genomics Suite software (Partek Inc.) essentially as described (36).…”
Section: Transcription Microarraymentioning
confidence: 99%